"Being Chinese Means Becoming Cheap Labour": Education, National Belonging and Social Positionality among Youth in Contemporary China. (24th March 2021) - Naftali, Orna
Abstract: Since the 1990s, the Chinese party-state has attempted to teach its youth how to think and speak about the nation through a "patriotic education" campaign waged in schools, the media and on public sites. The reception of these messages by youth of different social backgrounds remains a disputed issue, however. Drawing on a multi-sited field study conducted among rural and urban Han Chinese youth attending different types of schools, this article explores the effects of the patriotic education campaign on youth conceptions of the nation by examining the rhetoric high-school students employ when asked to reflect upon their nation. The study reveals that a majority of youth statements conform to the language and contents of the patriotic education campaign; however, there are significant differences in the discursive stances of urban youth and rural youth and of those attending academic and non-academic, vocational schools. These findings call into question the party-state's current vision of China as a "unified" national collectivity. They highlight the existence of variances in the sense of collective belonging and national identity of Chinese youth, while underscoring the importance of social positioning and perceived life chances in producing these variances.